2009
DOI: 10.1152/physiolgenomics.90276.2008
|View full text |Cite
|
Sign up to set email alerts
|

Persistent fetal infection with bovine viral diarrhea virus differentially affects maternal blood cell signal transduction pathways

Abstract: The consequences of viral infection during pregnancy include impact on fetal and maternal immune responses and on fetal development. Transplacental infection in cattle with noncytopathic bovine viral diarrhea virus (ncpBVDV) during early gestation results in persistently infected (PI) fetuses with life-long viremia and susceptibility to infections. Infection of the fetus during the third trimester or after birth leads to a transient infection cleared by a competent immune system. We hypothesized that ncpBVDV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 65 publications
(70 reference statements)
3
21
0
Order By: Relevance
“…This approach, unlike stringent selection of microarray probes, allowed for a better accounting of interactive genes which may not be statistically significant considered separately, but add strength to each other as a group. Pathway analysis has been proven effective for the analysis of metastasis biomarker association with cancer (31, 32) and for signal transduction relationships with infectious disease (32). Ingenuity Pathway Analysis (Ingenuity Systems Inc., Redwood City, CA) of the induced microarray dataset identified specific metabolic pathways that could be associated with between 16 to 32 individual genes.…”
Section: Resultsmentioning
confidence: 99%
“…This approach, unlike stringent selection of microarray probes, allowed for a better accounting of interactive genes which may not be statistically significant considered separately, but add strength to each other as a group. Pathway analysis has been proven effective for the analysis of metastasis biomarker association with cancer (31, 32) and for signal transduction relationships with infectious disease (32). Ingenuity Pathway Analysis (Ingenuity Systems Inc., Redwood City, CA) of the induced microarray dataset identified specific metabolic pathways that could be associated with between 16 to 32 individual genes.…”
Section: Resultsmentioning
confidence: 99%
“…27 There is upregulation of type I IFN in maternal blood of calves infected with ncp BVDV at day 175 of gestation. 138 Leukocytes from these dams with a PI fetus showed downregulation of T-cell receptor signaling and of CXCR4 (the receptor for the lymphocyte chemoattractant, stromal cell-derived factor 1). 15,123,138 It is these features of the BVDV proteins E rns and N pro that are thought to enable the virus to avoid the innate immune system in the early gestation fetus.…”
Section: Persistent Infectionmentioning
confidence: 97%
“…Upregulation of interferon-stimulated gene 15kD (ISG15) has been observed in the blood of pregnant cattle during the early stage of ncp BVDV infection both in early and middle gestation. 137,138 By day 45 postinoculation, ISG15 had returned to baseline in both the PI and transiently infected (TI) cows in PI mothers, using quantitative reverse transcription polymerase chain reaction (qRT-PCR). Further work has shown that ncp BVDV has effects on several families of chemokines.…”
Section: Persistent Infectionmentioning
confidence: 99%
“…Reproductive biology studies are also well represented (e.g. [101][102][103]), which was in comparison a very minor theme in human studies. As can be expected these themes are common to most species of economical relevance.…”
Section: Blood Transcriptome Profiling Studies In Health and Diseasementioning
confidence: 99%